All roads lead to Rome: the plasticity of gut microbiome drives the extensive adaptation of the Yarkand toad-headed agama (Phrynocephalus axillaris) to different altitudes - Du, Jianghao; Zheng, Peng; Gao, Weizhen; Liang, Qianru; Leng, Lin; Shi, Lei (Frontiers in Microbiology, 2025)
The gut microbiome was involved in a variety of physiological processes and played a key role in host environmental adaptation. However, the mechanisms of their response to altitudinal environmental changes remain unclear. In this study, we used 16S rRNA sequencing and LC-MS metabolomics to investigate the changes in the gut microbiome and metabolism of the Yarkand toad-headed agama (Phrynocephalus axillaris) at different altitudes (−80 m to 2000 m). The results demonstrated that Firmicutes, Bacteroidetes, and Proteobacteria were the dominant phylum, Lachnospiraceae and Oscillospiraceae were the most abundant family, and the low-altitude populations had higher richness than high-altitude populations; Akkermansiaceae appeared to be enriched in high-altitude populations and the relative abundance tended to increase with altitude. The gut microbiome of three populations of P. axillaris at different altitudes was clustered into two different enterotypes, low-altitude populations and high-altitude populations shared an enterotype dominated by Akkermansia, Kineothrix, Phocaeicola; intermediate-altitude populations had an enterotype dominated by Mesorhizobium, Bradyrhizobium. Metabolites involved in amino acid and lipid metabolism differed significantly at different altitudes. The above results suggest that gut microbiome plasticity drives the extensive adaptation of P. axillaris to multi-stress caused by different altitudes. With global warming, recognizing the adaptive capacity of wide-ranging species to altitude can help plan future conservation strategies.